Pengelasan SMAW dengan variasi g Perbandandingan Gerakan Elektroda Terhadap Uji Mikrostruktur, Uji Bending & Uji Impak Pada Pegas Daun Mitsubishi Canter 125 PS: Pengelasan SMAW, Gerakan Elektroda, Uji Mikrostruktur, Uji Bending, Uji Impak - ikhsan, ikhsan; Zulrian Aldio, Rieza (Universitas Muhammadiyah Metro, 2024)
Welding is a process of joining two metals, especially steel, to obtain a finished material connection in a liquid state. The aim of this research is to obtain bending strength, impact strength and microstructure in welding joints with various variations of spiral electrode movement, zig-zag and U electrode movement. The welding process uses a SMAW welding machine with a current of 90A, E7018 electrode wire with a diameter of 2.6 mm, the material used is SUP9A leaf spring steel which is made at an X angle of 60°. The results showed that impact testing with zig-zag electrode movement obtained the highest average impact value of 1.33 Joules/mm², while the highest average bending strength value was found in the U electrode movement of 111.2 MPa and the lowest bending strength value. In the zig-zag electrode movement, namely 97.4 MPa, in microstructure testing the zig-zag electrode movement has hard material properties because there is more pearlite phase dominant, in spiral and U electrode movements the material is soft because there is more ferrite phase dominant.